Strategi Komunikasi Pemasaran Lembaga Kursus - Indira Reihan Putri; Aning Sofyan Sadikin (UNISBA Press, 2023)
Abstract. South Korean culture is rife in Indonesia. Starting frommovies, dramas, and music. Many people want to learn Koreanafter watching movies, dramas, music, even boy group and girlgroup concerts from South Korea. Taeyang Kulture is one of theforums for language course institutions in Bandung and alreadyhas 6,280 students. The research method used is qualitative. The constructivism paradigm and the case study approach involveTaeyang Kulture's internal parties and external parties attendingKorean language events at Taeyang Kulture and are associatedwith marketing communication and event category theory. Thisstudy aims to determine the marketing communication strategycarried out by Taeyang Kulture. The subjects of this study were Taeyang Kulture's internal parties and external parties such as visitors who took part in the event. Abstrak. Kebudayaan Korea Selatan sedang marak di Indonesia. Mulai dari film, drama, dan musiknya. Banyak orang yang ingin mempelajari bahasa korea setelah menonton film, drama, musik, bahkan konser boy group dan girl group asal Korea Selatan. Taeyang Kulture menjadi salah satu wadah lembaga kursus bahasa yang berada di Bandung dan sudah memiliki sebanyak 6.280 murid. Metode penelitian yang digunakan kualitatif. Paradigma konstruktivisme dan , pendekatan studi kasus yang melibatkan pihak internal Taeyang Kulture dan pihak eksternal pengunjung event bahasa korea di Taeyang Kulture serta dikaitkan dengan teori kategori event dan komunikasi pemasaran. Penelitian ini bertujuan untuk mengetahui strategi komunikasi pemasaran yang dilakukan oleh Taeyang Kulture. Subjek dari penelitian ini adalah pihak internal Taeyang Kulture dan pihak eksternal seperti pengunjung yang menikuti event tersebut.